The phenotype range of achondrogenesis 1A. Issue 10 (16th August 2013) - Grigelioniene, Giedre; Geiberger, Stefan; Papadogiannakis, Nikos; Mäkitie, Outi; Nishimura, Gen; Nordgren, Ann; Conner, Peter
Abstract Achondrogenesis 1A (ACG1A; OMIM 200600) is an autosomal recessive perinatally lethal skeletal dysplasia comprising intrauterine growth failure, micromelia, minor facial anomalies, deficient ossification of the skull, absent or extremely defective spinal ossification, short beaded ribs, and short deformed long bones with a stellate appearance. ACG1A is caused by mutations in the TRIP11 gene, resulting in deficiency of the Golgi microtubule associated protein 210. In this study we describe dizygotic twins with a clinical and radiological phenotype of ACG1A who were homozygous for a novel nonsense mutation in the TRIP11 gene. In addition, another patient with a milder manifestation, not readily distinguishable from those of other lethal skeletal dysplasias, was found to be a compound heterozygote for a nonsense mutation and a deletion of the 3′ end of the TRIP11 gene. We conclude that mutations of the TRIP11 gene may encompass a wider phenotypic range than previously recognized. © 2013 Wiley Periodicals, Inc.